THE EFFECT OF A VIDEO-AID CONTEXTUAL APPROACH TO THE EFFORTS OF IMPROVING THE ABILITY OF WRITING STORY TEXT IN CLASS IX JUNIOR HIGH SCHOOLS - Rivaldi Ramadhan (JLER (Journal of Language Education Research), 2022)
The students' difficulties in understanding the material and the lack of interest in learning in learning to write short story texts were the background for this research to be conducted. A contextual approach assisted by instructional video media is used to overcome this problem. The formulation of the problem is whether there is an effect of using contextual approaches assisted by instructional videos on students' abilities in learning to write short story texts. The method used in this research is quantitative descriptive method using written test instruments as a tool to determine students' writing skills. Following are the results of the average score that students have at the time of the pretest getting 60.32 and the posttest getting 75.54, it can be seen that there is an increase in the value of 15.22 points. In line with the results of the paired sample test, which obtained a significance value (2-tailed) of 0.000 <0.005, it means that Ha is accepted. So it can be concluded that the use of a contextual approach assisted by instructional videos in learning to write short story texts can improve students' writing skills.